2010
DOI: 10.2478/v10011-010-0031-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Analytical Workstations as a Tool for Reducing Laboratory Errors

Abstract: Kratak sadr`aj: Redukcija gre{aka i pobolj{anje kvaliteta su integralni deo laboratorijske medicine. Laboratorijsko testi r anje, vrlo slo`en postupak koji se ~esto naziva procesom totalnog testiranja (TTP), obi~no se deli na tri tradicio nalne faze: pre-analiti~ku, intra-analiti~ku i post-ana liti~ku. Niz radova objavljenih po~ev od 1989. skrenuo je pa`nju laboratorijskih stru~njaka na pre-analiti~ku fazu, koja se trenutno ~ini najpodlo`nijom gre{kama. Stoga bi pre-ana li ti~ka faza trebalo da bude glavna met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
10
0
4
Order By: Relevance
“…However, up to 0.5% of all laboratory test-results have been estimated to be erroneous and one fourth of these errors have consequences for the patient, which include a delayed test result or new sample collection, but may also have a life threatening impact and tragic consequences, such as the administration of unnecessary chemotherapy or the onset of coma. The dependence of patient management on laboratory data highlights the need for ensuring the quality of these services [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, up to 0.5% of all laboratory test-results have been estimated to be erroneous and one fourth of these errors have consequences for the patient, which include a delayed test result or new sample collection, but may also have a life threatening impact and tragic consequences, such as the administration of unnecessary chemotherapy or the onset of coma. The dependence of patient management on laboratory data highlights the need for ensuring the quality of these services [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian ini bertujuan untuk mengetahui tingkat terutama dalam hal penegakan diagnosis, tindak lanjut pengetahuan, sikap, dan perilaku perawat tentang pengobatan, monitoring, keputusan rawat inap serta tindakan flebotomi serta pengaruhnya terhadap kualitas pasien pulang (1)(2)(3). Oleh karena itu peningkatan mutu spesimen laboratorium.…”
Section: Pendahuluanunclassified
“…Uji korelasi digunakan untuk menganalisis container atau jenis antikoagulan, rasio volume spesimen hubungan antara tingkat pengetahuan dan kualitas dan antikoagulan yang tidak sesuai, spesimen darah spesimen. Untuk menganalisis hubungan antara perilaku diambil dari jalur infus (1,(3)(4)(5)(6). Data tersebut perawat (patuh atau tidak patuh SPO) dan kualitas memperlihatkan bahwa kesalahan pra-analitik yang spesimen (layak atau tidak layak) digunakan uji statistik paling banyak yaitu kesalahan yang berhubungan dengan Chi-Square dengan tingkat kepercayaan 95%.…”
Section: Pendahuluanunclassified
“…Pre-analytical error and post-analytical error data are well documented. Occurrence of the errors at the pre-and post-analytical phases currently appears to be more vulnerable than the analytical phase [2]. Studies revealed that 46%-68.2% of laboratory errors predominated in the pre-analytical phase, and 18.5%-47% errors recorded in the post-analytical phase of the laboratory testing process [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%